(untitled) (Legal journal - Research in Legal and Social Sciences, 2018)
The present paper explores the indirect perpetration through an organized apparatus of power`s theory, in the current legal system, developed by the german jurist Claux Roxin (1963). The legal concept emerges as a new form of criminal participation, with the aim of filling up the legal vacuum, left by the restrictive concept of perpetrator, valid at that time in Germany. In that sense, the paraguayan Penal Code adopts the theory of control of events, regarding authorship -direct, indirect, and co-authorship- and takes the author`s restrictive concept, splitting the criminal participation into three parts. In this respect, the Penal Code sets the author as central figure in the accomplishment of the criminal offense, since this fullfills the rule of law; and grants inductors and accomplices a second role, given the fact that these are punished merely by extension. The new form of criminal participation proposed by Roxin, implies a change of concept in the criminal behavior`s ontological structure, and that is why it turns necessary to analyse his assumptions more closely.